Morphological and Structural Studiesof ZnO Micro-Nanorod Structures Synthesized Using a Low-Cost Hydrothermal Method - Alfarisa, Suhufa; Toruan, Parmin Lumban; Atina, Atina; Dwandaru, Wipsar Sunu Brams; Safitri, Rika Noor (UI Scholars Hub, 2018)
Micro-nanorod structuresof zincoxide (ZnO) have been successfully synthesized via a simple and low-cost hydrothermal method. ZnO solutions with different concentrations of 0.05 and 0.1 M were prepared using zinc nitrate tetrahydrate and hexamethylenetetramine precursors. They were dissolved inaquadesand stirred before the hydrothermal process at 95 °C for 4 hours in an oven. Extensive characterizations using scanning electron microscope (SEM) and X-ray diffraction (XRD) were conductedon ZnO powder samples. SEM results showed that hexagonally shaped ZnO micro-nanorods were formed with diameters ranging from hundreds of nanometers to several micrometers. The ZnO sample synthesized at 0.05 M was observedto have a better surface morphological structurethan the 0.1 M sample. In addition, XRD measurements confirmed that samples exhibited a hexagonal crystal structure of ZnO. Moreover, the calculated crystallite sizes of ZnO using the Debye-Scherrer equation using the full-width half maxima of the XRD peaks were 25.153 nm for the 0.05 M sample and 28.707 nm for the 0.1 M sample. The most prominent growth of ZnO had 101 plane orientation or nonpolara-plane followed by nonpolar 100 m-plane and 002 polar c-plane orientations.This studyoffersa simple andlow-costroute to producehigh-quality ZnO micro-nanorods for use in various electrical and optical devices.